"Nullification through armed civil disobedience": a case study of strategic framing in the patriot/militia movement. Issue 1 (2nd January 2019) - Jackson, Sam
ABSTRACT: The patriot/militia movement in the US has grown in prominence over the past several years, with the movement engaging in high-profile conflicts with law enforcement (e.g., at the Bundy Ranch standoff in Nevada in 2014) and political opponents (e.g., clashing with antifascist activists in Boston and Berkeley in 2017). One of the strategies movement leaders use to solicit support is to ground their goals and behaviour in American history. This article presents a case study of one striking example of this, where a leading figure in the movement (Mike Vanderboegh, who popularized the idea of the Three Percenters) attempted to justify his advocacy of violating the law by simultaneously claiming the legal legitimacy of nullification and the moral legitimacy of civil disobedience. I argue that this rhetoric is an example of strategic frame appropriation. This type of frame appropriation serves the purpose of legitimating violent resistance to government by drawing parallels to other forms of political activism that are widely respected.